Comparison of the effect of lecture and role-playing methods on awareness of healthy nutrition in school-age children - Samane Najafi; Mohammad Reza Mansoorian; Shahla Khosravan; Nemat Jafari Ghaleh Joughi; Sima Jafari Ani; Fatemeh Khalili (Tehran University of Medical Sciences, 2020)
Background & Aim: The healthy nutrition education is one of the most important priorities in all life periods, especially in childhood. The teaching method is also considered one of the important factors for the effectiveness of education. Therefore, the aim of this study was to compare the effect of lecture and role-playing methods on awareness of healthy nutrition in school-age children. Methods & Materials: This quasi-experimental study was conducted on 60 primary school students in Gonabad city in 2017. Participants were selected by multistage random sampling and allocated into two groups of role-playing and lecture. Studentschr('39') awareness was measured by a self-structured questionnaire before, immediately and one month after education. Data were analyzed using the SPSS software version 16 by descriptive and inferential statistics. A P-value less than 0.05 was considered significant. Results: The mean score of awareness for the role-playing group before, immediately and one month after the intervention respectively was 10.77±2.55, 14.1±55.15 and 14.50±1.10 and for the lecture group respectively was 11.07±1.85, 13.72±1.43 and 11.47±2.84 (the score range: 0-16). There was a significant difference in the mean score of awareness before, immediately and one month after the intervention between the two groups (P<0.001), and in the role-playing group, the increase in awareness score was more than in the lecture group. Conclusion: Considering the greater effect of role-playing method than lecture on healthy nutrition education in school-age children, it is suggested that more attractive, dynamic and effective methods such as role-playing, in accordance with educational behavioral goals, be used in school nutrition education programs. In addition to enhancing educational efficiency, this will make the effects of education and learning more sustainable for students.